Prevalence of multidrug-resistant Acinetobacter baumannii and Pseudomonas aeruginosa in an Italian hospital - M.A. De Francesco; G. Ravizzola; L. Peroni; C. Bonfanti; N. Manca (Elsevier, 2013)
Summary: The severity and extent of disease caused by multidrug-resistant organisms (MDROs) varies by the population(s) affected and the institution(s) at which these organisms are found; therefore, preventing and controlling MDROs are extremely important.A retrospective study of patients who were infected with Acinetobacter baumannii or Pseudomonas aeruginosa was performed at the Spedali Civili Hospital in Brescia, Italy, from 2007 to 2010.A total of 167 (0.52%) A. baumannii isolates and 2797 P. aeruginosa (8.7%) isolates were identified among 31,850 isolates.Amikacin and colistin were the most active agents against A. baumannii strains. Multidrug resistance (MDR) was observed in 57 isolates (54%). Most MDR isolates (42 out of 57, 73%) were resistant to four classes of antibiotics.P. aeruginosa was recovered more frequently from the respiratory tract, followed by the skin/soft tissue, urine and blood.Colistin, amikacin and piperacillin/tazobactam were active against 100%, 86% and 75% of P. aeruginosa isolates, respectively. A total of 20% (n = 316) of P. aeruginosa isolates were MDR. In summary, A. baumannii was more rare than P. aeruginosa but was more commonly MDR.Epidemiological data will help to implement better infection control strategies, and developing a local antibiogram database will improve the knowledge of antimicrobial resistance patterns in our region. Keywords: P. aeruginosa, A. baumannii, Antibiotic resistance, Infection, Antibiotics